Research on the Route of Integrating Cultural Confidence into Corporate Culture Construction under the Background of Cultural Power (Journal of science and technology exploration, 2026)
Corporate culture is the spiritual strength of enterprise development, and cultural confidence is an important guarantee for the cohesion and soul building of corporate culture. Integrating cultural confidence into the construction of corporate culture in China under the background of building a strong cultural nation can help guide enterprises to establish correct business concepts and values, and promote their development towards a healthy and sustainable direction. Firstly, based on a brief description of the connotation of cultural confidence, the importance of cultural confidence in corporate culture construction is proposed. Then, from the perspective of cultural confidence, this article elaborates on the problems in the construction of corporate culture in China from five aspects: traditional culture, advanced culture, regional culture, personal culture, and employee culture. Finally, it is pointed out that the integration of corporate culture construction into cultural confidence needs to be promoted collaboratively from three levels: ideology, system, and practice, and specific integration paths are proposed.
Keywords: Cultural power; Cultural confidence; Corporate culture; Integration; Route